Influence of various base nanofluids and substrate materials on heat transfer in trapezoidal microchannel heat sinks - Mohammed H.A.; Gunnasegaran P.; Shuaib N.H. (2023)
Numerical investigations are performed to investigate the laminar flow and heat transfer characteristics of trapezoidal MCHS using various types of base nanofluids and various MCHS substrate materials on MCHS performance. This study considered four types of base fluids including water, ethylene glycol (EG), oil, and glycerin with 2% volume fraction of diamond nanoparticle, and four types of MCHS substrate materials including copper, aluminium, steel, and titanium. The three-dimensional steady, laminar flow and heat transfer governing equations are solved using the finite volume method. It is found that the best uniformities in heat transfer coefficient and temperature among the four mixture flows can be obtained using glycerin-base nanofluid followed by oil-base nanofluid, EG-base nanofluid, and water-base nanofluid heat sinks. However, the heat transfer performance of water-base nanofluid can be greatly enhanced in steel made substrate heat sink. 2010 Elsevier Ltd.